Prevalence of Diabetes and Its Determinants in the Young Adults Indian Population-Call for Yoga Intervention - Nagarathna, Raghuram; Bali, Parul; Anand, Akshay; Srivastava, Vinod; Patil, Suchitra; Sharma, Guruprasad; Manasa, Krishna; Pannu, Viraaj; Singh, Amit; Nagendra, Hongasandra R. (Frontiers in Endocrinology, 2020)
Background: Young Indian population that constitutes 65% of the country is fast adapting to a new lifestyle not known earlier and is at a high-risk of the increasing burden of diabetes and associated complications. The new evolving lifestyle is not only affecting people’s health but also mounting the monetary burden on the developing country like India. Aim: We aimed to collect information regarding the prevalence of risk of diabetes in the young adults (<35years) in 30 most populous states and union territories (7 zones) of India, using a validated questionnaire. Methods: A user-friendly Indian Diabetes Risk Score based survey was conducted across India by trained personnel in 58,821 young individuals. The prevalence of low, moderate and high risk of diabetes was estimated, and its correlation with associated risk factors, such as age, physical activities, yoga, family history, body vitals, diets, gender, marriage, education, occupation, and socioeconomic status, in young adults was determined. Results and Conclusions: The prevalence of self-reported diabetes in Indian young adults (<35years) was 1.8% with a small difference between men (1.7%) and women (1.9%). The highest number of self-reported cases of diabetes in young Indians was in the South Zone (2.5%) with similar proportions in males and females. The prevalence of diabetes was highest among those with parental history of diabetes and among married couples.